2022
DOI: 10.1101/2022.04.27.489727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSP90.6 is involved in grain filling via carbon and nitrogen metabolism in maize

Abstract: Carbon and nitrogen are the two most abundant nutrients in all living things, and their metabolism maintains normal plant growth. However, the molecular mechanism underlying carbon and nitrogen metabolism remains largely unknown. Here, we found that HSP90.6 is involved in the metabolism of carbon and nitrogen. We performed gene cloning and functional characterization of a maize EMS mutant ehsp90.6, whose kernels were small. HSP90.6 encodes heat shock protein 90.6, which has a single-amino acid mutation within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Recent advances in meta‐genomics techniques have provided insightful genomic information and diversity associated with C and N metabolism 148,149 . Numerous studies involving quantitative trait loci (QTL) have been conducted to unravel the C and N metabolism in various plant species 150–152 .…”
Section: Employing Omics Technologies In Carbon and Nitrogen Metaboli...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in meta‐genomics techniques have provided insightful genomic information and diversity associated with C and N metabolism 148,149 . Numerous studies involving quantitative trait loci (QTL) have been conducted to unravel the C and N metabolism in various plant species 150–152 .…”
Section: Employing Omics Technologies In Carbon and Nitrogen Metaboli...mentioning
confidence: 99%
“…Recent advances in meta-genomics techniques have provided insightful genomic information and diversity associated with C and N metabolism. 148,149 Numerous studies involving quantitative trait loci (QTL) have been conducted to unravel the C and N metabolism in various plant species. [150][151][152] These studies have identified specific genetic regions modulating C and N metabolic processes in plants, including nitrogen use efficiency (NUE) and photosynthesis.…”
Section: Genomicsmentioning
confidence: 99%